Authoritarian populism, neo-fascism and 2022 national elections: Agrarian implications from the advance of the extreme right in Brazil (REVISTA NERA, 2022)
Bolsonaro was elected in 2018 with a very conservative political agenda, promising neoliberal economic measures, and opposing to minority’s rights. Bolsonaro has been well-known as a right-wing and authoritarian politician and his government is recognised as extreme right, conservative, and/or neo-fascist, with important setbacks in public policies. The ‘bolsonarismo’ shall be defeated, but the electoral process will not be easy, with fake news. The open threats to democracy are leading to alliances of democratic and popular political forces, including agrarian and urban social movements. This article reflects critically about Bolsonaro administration, particularly the dismantling of public policies, reflecting about the political actions of the agrarian movements in the 2022 electoral process.